The effect of different dosing strategies of sodium bicarbonate upon collegiate swimmers - Bowman, Steven A. (My University, 2002)
This study evaluated the efficacy of different dosages of sodium bicarbonate on time trial performance, blood lactate concentrations and incurred side effects. Participants included 10 volunteer male (n = 3) and female (n = 7) members of the University of Wisconsin-La Crosse swimming team. The participants were divided into groups by in-season specialization of 100 yards, 200 yards or 400 yards. Each participant completed a time trial under a control condition, and under 0.1 g/kg body weight, 0.2 g/kg body weight and 0.3 g/kg body weight. Blood lactate was collected before and after the time trial. Side effects were recorded every 10 minutes from consumption to 20 minutes post trial. Performance times were all significantly faster under the experimental conditions vs. control (p = 0.001). The 0.1 g/kg body weight produced the fastest time (97% of the control time), then 0.2 g/kg body weight (98.19% of the control time) and 0.3 g/kg body weight (99.10% of the control time). Pre and post-trial lactate values all increased proportionately with the dosage of sodium bicarbonate and were significantly higher. than the control values in both pre-trial (p = 0.02) and post-trial (p = 0.001). Side effects were similar in type and frequency under the 0.1 g/kg body weight (7) and 0.2 g/kg body weight (10) conditions, however they increased in severity under the 0.3 g/kg body weight (27) condition. The findings suggest that bicarbonate loading is effective even at lower dosages, however, as the dosage increases, side effects can impede any ergogenic effect. Reduced water consumption during dosing may help to avoid gastro-intestinal side effects.
Keywords: Sodium bicarbonate - Physiological effect; Swimming - Physiological aspects